Regional Government Strategy in Realizing Independent Village Development in Banjar Regency - Nicola, Rahmad Nanda; Muharam, Samahuddin; Maryono, Maryono (International Journal Labs, 2025)
This research explores the challenges and strategies for achieving independent villages (desa mandiri) in Banjar Regency, South Kalimantan, Indonesia. Despite significant government support through Village Funds (Dana Desa) as mandated by Law No. 6 of 2014, Banjar Regency remains the second lowest in the Indeks Desa Membangun (IDM) ranking due to underutilized local potential, low human resource quality, and weak institutional management. Using a qualitative descriptive approach with triangulation methods—interviews with key informants from the Village Community Empowerment Office (DPMD), field observations, and document analysis—this study identifies both internal and external factors influencing the development of independent villages. SWOT analysis reveals internal weaknesses such as limited digital literacy, inadequate participation of the community, and underdeveloped BUMDes (village-owned enterprises), along with external challenges like infrastructure gaps and market access limitations. To address these issues, five key strategies are proposed: (1) developing agriculture and livestock sectors through technology and digital training; (2) strengthening cooperation with universities and NGOs for capacity building; (3) optimizing BUMDes to manage and market village products digitally; (4) integrating village institutions with government and private training programs to enhance professionalism; and (5) leveraging regulations and government support to open market access and promote local agro-tourism. The results provide a strategic framework to accelerate village independence by combining technological innovation, institutional empowerment, and sustainable economic development.